If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (78x + -48y) + -1(68x + 28y) = 0 Remove parenthesis around (78x + -48y) 78x + -48y + -1(68x + 28y) = 0 78x + -48y + (68x * -1 + 28y * -1) = 0 78x + -48y + (-68x + -28y) = 0 Reorder the terms: 78x + -68x + -48y + -28y = 0 Combine like terms: 78x + -68x = 10x 10x + -48y + -28y = 0 Combine like terms: -48y + -28y = -76y 10x + -76y = 0 Solving 10x + -76y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '76y' to each side of the equation. 10x + -76y + 76y = 0 + 76y Combine like terms: -76y + 76y = 0 10x + 0 = 0 + 76y 10x = 0 + 76y Remove the zero: 10x = 76y Divide each side by '10'. x = 7.6y Simplifying x = 7.6y
| -x+5y-3x-2y= | | 4(5y+7z)-28z= | | 5/13+6/11 | | 2(6y+2z)-4z= | | k+-9k-8k-10k=-20 | | 5y(2y-4)+14y= | | 9a-3(a+3)= | | 8c-10c-6=10 | | -1a-24=5a | | 2x+7(8+2x)=8 | | 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= | | -(2x^2-7x+7)= | | 4y(3y-6)+19y= | | A=8*(3.14) | | 4x-6=4(x+5) | | (63x+45y)-(13x+40y)= | | 6(x-6)+20=2(x-6) | | -(12b-10)+5(3b-2)= | | 8x+3=-3+3x+21 |